Peran Psikologi Agama dalam Pembentukan Karakter Profetik Peserta Didik - Ratu Rinindya Ramadhani Zahfi; Yuminah Rohmatullah (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
This study aims to determine the role of psychology of religion in the development of prophetic character in students is to understand the psychology of religion influences or plays a role either in general or in the development of prophetic values that exist in students. This research uses a literature study method where researchers read theories related to the problems studied which are sourced from academic literature. The results of the study show that education is a means in shaping the religious spirit of students. Psychology of Religion has a role to develop the prophetic nature of learners by providing awareness of the meaning of life, the purpose of their actions by improving morals and ethics in everyday life, relationships with God in the form of strengthening beliefs and faith. A learner can face the challenges of faith with emotional control. The conclusion of this study shows that the psychology of religion has a very important role in the formation of the prophetic character of students with the help of the psychology of religion students can understand the meaning of religious prophetic values that will be the basis for the formation of character and personality behavior of each student to achieve the welfare of life.